If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2k + -1r = 15 Solving 2k + -1r = 15 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add 'r' to each side of the equation. 2k + -1r + r = 15 + r Combine like terms: -1r + r = 0 2k + 0 = 15 + r 2k = 15 + r Divide each side by '2'. k = 7.5 + 0.5r Simplifying k = 7.5 + 0.5r
| 2z-3(2+1)=-(52+3)+2 | | -7*2.9= | | 4.43b+3.42f= | | 5/2v+1/3=23/4 | | -7y+2x= | | 16(8c-1)-14=126c+16 | | 3y-5=-17 | | 8x=21x | | -5k+9k=2 | | y-28wheny=46 | | (3+2j)(-2+4j)= | | 4(2x+9)=18-2(x-9) | | 2x^4-8x^2-10x=0 | | -5(2)+9k=2 | | 3(x+2)=-5-2(x+3) | | 1/6(7t-4)=t+4/12 | | 2x^4+8x^2+10x=0 | | 1/9x+1/5x+2/9=38/45 | | (x^3)-8=0 | | 27-9(-8x-5)=648x+432 | | 5y-2(y+5)=-(2y+15) | | 7(-4x+3)=-91 | | 9[3-(-8x-5)]=648x+432 | | 8-(6-6n)+9=-2+12(n+1) | | 42=6/7y | | K-73=91 | | 9[3-(8x-5)]=648x+432 | | 3a(2a-5)=13-2(a+2) | | W+110=763 | | 3(x+6)(x+12)=75 | | 9x-6x+5=x-8+13 | | 3a(2a-5)=13-2(a+12) |